The Postmodernism Approach In Preventing Multicultural Conflict - Syahri Ramadhan; Melly Tria Utari (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
Indonesia as a country inhabited by multicultural societies has diversity in aspects of the nation's culture. The diversity of Indonesian society is what makes the country of Indonesia very vulnerable to conflicts that include fights between groups of residents, fights between villages, fights between citizens and officials, fights between students and fights between tribes. The purpose of this paper is to examine the relevance of postmodernism in preventing multicultural conflict. The findings concluded by writers from various literary sources explain that postmodernism thinking is still very relevant to be used in everyday life in society at the time of digitalization at this time. With the postmodernism thinking, it can instill the nature of mutual respect, tolerance, and be wise in dealing with a problem, differences of opinion, as well as differences in cultural diversity of the Indonesian nation, through instilling the values ​​of pluralism, deconstructiveism, and relativism. Implementation strategies of postmodernism thinking can be done in various ways, one of which is by means of education, namely through the formal education approach method, namely schools that start from kindergarten to tertiary level. The application of postmodernism thinking in schools is integrated in three ways, school culture programs, self-development, and namely the integration of subjects.